2009
DOI: 10.1111/j.1750-3841.2009.01277.x
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antimicrobial and Antioxidant Activities of Essential Oils and Various Extracts of Juniperus phoenicea L. (Cupressacees)

Abstract: GC-FID and GC-MS analysis of essential oils of Juniperus phoenicea resulted in the identification of 30 compounds, representing more than 98% of the total composition. alpha-pinene (55.7% and 80.7%), delta-3-carene (10.7% and 4.5%), and gamma-cadinene (2.9% and 5.1%) were the main components, respectively, in leaves and berries essential oil. Extracts of J. phoenicea were obtained by different extraction solvents: methanol, ethanol, ethyl acetate, and dichloromethane and evaluated composition for polyphenols (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
60
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(71 citation statements)
references
References 31 publications
10
60
1
Order By: Relevance
“…a-Pinene Agar diffusion test [107] A. niger, Rhizopus oryzae Laurus nobilis [46] A. niger Matricaria chamomilla L.(Asteraceae) a-Bisabolol (56.9%) - [194] A. ochraceus, M. ramamnianus Mentha longifolia L. (Lamiaceae) Pulegone (54.4%) Diffusion test [109] A. ochraceus, M. ramamnianus Mentha viridis L. (Lamiaceae) Carvone (50.5%) Diffusion test [109] Cladosporium cladosporioides Myrica gale L. (Myricaceae) a-Pinene; germacrone Dilution test [195] A. flavus, Fusarium tabacinum, Fusarium solani Nepeta cataria L. (Lamiaceae) 4aa,7a,7ab-Nepetalactone (70.4%)…”
Section: Juniperus Phoenicea L (Cupressaceae)mentioning
confidence: 99%
“…a-Pinene Agar diffusion test [107] A. niger, Rhizopus oryzae Laurus nobilis [46] A. niger Matricaria chamomilla L.(Asteraceae) a-Bisabolol (56.9%) - [194] A. ochraceus, M. ramamnianus Mentha longifolia L. (Lamiaceae) Pulegone (54.4%) Diffusion test [109] A. ochraceus, M. ramamnianus Mentha viridis L. (Lamiaceae) Carvone (50.5%) Diffusion test [109] Cladosporium cladosporioides Myrica gale L. (Myricaceae) a-Pinene; germacrone Dilution test [195] A. flavus, Fusarium tabacinum, Fusarium solani Nepeta cataria L. (Lamiaceae) 4aa,7a,7ab-Nepetalactone (70.4%)…”
Section: Juniperus Phoenicea L (Cupressaceae)mentioning
confidence: 99%
“…I 680 580 520 450 II 955 800 960 810 III 940 670 735 650 Moreover, the antibacterial activity of the EO of J. phoenicea could be associated with major constituents such as α-pinene, δ-3-carene, α-terpineol, β-myrcene, limonene, γ -terpinene, and α-amorphene. These components have been reported to display antibacterial effects (Ennajar, et al, 2009). In addition, the results of antibacterial activity of EOs isolated from C. sempervirens showed that the oils inhibited the growth of bacterial strains with lower MIC values from 390 to 585 mg/L for all bacteria depended on susceptibility of the tested bacteria.…”
Section: Chemical Composition Of Essential Oils Of C Sempervirensmentioning
confidence: 95%
“…Many literatures reported that minor components have a critical part to play in antibacterial activity, possibly by causing a synergistic effect between other components (Bekhechi et al, 2008;Ennajar et al, 2009;Mazari1 et al, 2010 andFekih, et al, 2014). I 680 580 520 450 II 955 800 960 810 III 940 670 735 650 Moreover, the antibacterial activity of the EO of J. phoenicea could be associated with major constituents such as α-pinene, δ-3-carene, α-terpineol, β-myrcene, limonene, γ -terpinene, and α-amorphene.…”
Section: Chemical Composition Of Essential Oils Of C Sempervirensmentioning
confidence: 99%
“…Using antioxidant based formulation in animal feeding can be important to control oxidative process in meat and meat products. These help in disruption of the oxidation chain reaction that further progress with a passage of time which ultimately reduces the quality of meat-based products (Ennajar et al, 2009). However, according to Altmann et al (1986) synthetic antioxidants such as butylated hydroxyanisole (BHA) and butylated hydroxytoluene (BHT) that are generally used to slow or minimize oxidative deterioration of foods have been rejected because of their carcinogen effects.…”
Section: Introductionmentioning
confidence: 99%